(untitled) (Experimental biology, 2022)
Under the influence of intensifying physical loads, energy processes in the body intensify, and the amount of oxygen transported to the body increases. As with most oxidative stress factors, the main focus of the article is that there is a strong relationship between the changes in the products of oxidation of lipids in the skeletal muscles of the body and the adaptation processes that occur in the body as a result of regular exercise loads. It has been shown that it is of great diagnostic importance to determine the nature of LPO changes in adaptive physical loads in adaptive reactions, as the use of modern non-invasive, painless and convenient methods in the use of modern functional and laboratory diagnostics is accelerated. Based on the biochemical analysis of oral water, it also allows to assess the capacity of the adaptation levels and to conduct more extensive studies. In this regard, the biochemical changes in the amount of LPO products used in the physical loads of 10-15 years old footballers in different age groups have also been investigated.